Potassium Titanyl Phosphate Material Engineering Boosting Integrated Optical Source Performance - Eigner, Christof; Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine (CLEO 2023)
We study the interaction of gray tracking and DC ionic conductivity in Potassium Titanyl Phosphate (KTiOPO 4 , KTP) and present a novel way to reduce conductivity via a potassium nitrate treatment improving the device quality.

(Photo-)electrochemical reactions on semiconductor surfaces, part B: III-V surfaces–atomic and electronic structure - Hajduk, Andreas; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Guidat, Margot; Löw, Mario; Ullmann, Fabian; Moritz, Dominik C.; Hofmann, Jan P.; Krischok, Stefan; Runge, Erich; Schmidt, Wolf Gero; Jaegermann, Wolfram; et al. (Encyclopedia of Solid-Liquid Interfaces)

Shallow Water DG Simulations on FPGAs: Design and Comparison of a Novel Code Generation Pipeline - Alt, Christoph; Kenter, Tobias; Faghih-Naini, Sara; Faj, Jennifer; Opdenhövel, Jan-Oliver; Plessl, Christian; Aizinger, Vadym; Hönig, Jan; Köstler, Harald (Lecture Notes in Computer Science)

Mutation Tree Reconstruction of Tumor Cells on FPGAs Using a Bit-Level Matrix Representation - Opdenhövel, Jan-Oliver; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies (HEART))

Early time behavior of spatial and momentum anisotropies in kinetic theory across different Knudsen numbers - Borghini, Nicolas; Borrell, Marc; Roch, Hendrik (arXiv:2201.13294)
We investigate the early time development of the anisotropic transverse flow and spatial eccentricities of a fireball with various particle-based transport approaches using a fixed initial condition. In numerical simulations ranging from the quasi-collisionless case to the hydrodynamic regime, we find that the onset of $v_n$ and of related measures of anisotropic flow can be described with a simple power-law ansatz, with an exponent that depends on the amount of rescatterings in the system. In the few-rescatterings regime we perform semi-analytical calculations, based on a systematic expansion in powers of time and the cross section, which can reproduce the numerical findings.

Even anisotropic-flow harmonics are from Venus, odd ones are from Mars - Bachmann, Benedikt; Borghini, Nicolas; Feld, Nina; Roch, Hendrik (arXiv:2203.13306)
We test the ability of the "escape mechanism" to create the anisotropic flow observed in high-energy nuclear collisions. We compare the flow harmonics $v_n$ in the few-rescatterings regime from two types of transport simulations, with $2→ 2$ and $2→ 0$ collision kernels respectively, and from analytical calculations neglecting the gain term of the Boltzmann equation. We find that the even flow harmonics are similar in the three approaches, while the odd harmonics differ significantly.

Linearly shifting ferromagnetic resonance response of La0.7Sr0.3MnO3 thin film for body temperature sensors - Hou, W; Yao, Y; Li, Y; Peng, B; Shi, K; Zhou, Z; Pan, J; Liu, M; Hu, J (Frontiers of materials science)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)

Bringing Massive Parallelism and Hardware Acceleration to Linear Scaling Density Functional Theory Through Targeted Approximations - Lass, Michael

Stable bipolarons in open quantum systems - Moroder, Mattia; Grundner, Martin; Damanet, François; Schollwöck, Ulrich; Mardazad, Sam; Flannigan, Stuart; Köhler, Thomas; Paeckel, Sebastian (Physical Review B 107, 214310 (2023))
Recent advances in numerical methods significantly pushed forward the understanding of electrons coupled to quantized lattice vibrations. At this stage, it becomes increasingly important to also account for the effects of physically inevitable environments. In particular, we study the transport properties of the Hubbard-Holstein Hamiltonian that models a large class of materials characterized by strong electron-phonon coupling, in contact with a dissipative environment. Even in the one-dimensional and isolated case, simulating the quantum dynamics of such a system with high accuracy is very challenging due to the infinite dimensionality of the phononic Hilbert spaces. For this reason, the effects of dissipation on the conductance properties of such systems have not been investigated systematically so far. We combine the non-Markovian hierarchy of pure states method and the Markovian quantum jumps method with the newly introduced projected purified density-matrix renormalization group, creating powerful tensor-network methods for dissipative quantum many-body systems. Investigating their numerical properties, we find a significant speedup up to a factor $\sim 30$ compared to conventional tensor-network techniques. We apply these methods to study dissipative quenches, aiming for an in-depth understanding of the formation, stability, and quasi-particle properties of bipolarons. Surprisingly, our results show that in the metallic phase dissipation localizes the bipolarons, which is reminiscent of an indirect quantum Zeno effect. However, the bipolaronic binding energy remains mainly unaffected, even in the presence of strong dissipation, exhibiting remarkable bipolaron stability. These findings shed light on the problem of designing real materials exhibiting phonon-mediated high-$T_C$ superconductivity.

Statistical analysis of initial state and final state response in heavy-ion collisions - Borghini, Nicolas; Borrell, Marc; Feld, Nina; Roch, Hendrik; Schlichting, Sören; Werthmann, Clemens (Phys. Rev. C 107 (2023) 034905)
We develop a general decomposition of an ensemble of initial density profiles in terms of an average state and a basis of modes that represent the event-by-event fluctuations of the initial state. The basis is determined such that the probability distributions of the amplitudes of different modes are uncorrelated. Based on this decomposition, we quantify the different types and probabilities of event-by-event fluctuations in Glauber and Saturation models and investigate how the various modes affect different characteristics of the initial state. We perform simulations of the dynamical evolution with KoMPoST and MUSIC to investigate the impact of the modes on final-state observables and their correlations.

Plant mitochondrial RNA editing factors can perform targeted C-to-U editing of nuclear transcripts in human cells - Lesch, Elena; Schilling, Maximilian T; Brenner, Sarah; Yang, Yingying; Gruss, Oliver J; Knoop, Volker; Schallenberg-Rüdinger, Mareike (Nucleic Acids Research)
Abstract RNA editing processes are strikingly different in animals and plants. Up to thousands of specific cytidines are converted into uridines in plant chloroplasts and mitochondria whereas up to millions of adenosines are converted into inosines in animal nucleo-cytosolic RNAs. It is unknown whether these two different RNA editing machineries are mutually incompatible. RNA-binding pentatricopeptide repeat (PPR) proteins are the key factors of plant organelle cytidine-to-uridine RNA editing. The complete absence of PPR mediated editing of cytosolic RNAs might be due to a yet unknown barrier that prevents its activity in the cytosol. Here, we transferred two plant mitochondrial PPR-type editing factors into human cell lines to explore whether they could operate in the nucleo-cytosolic environment. PPR56 and PPR65 not only faithfully edited their native, co-transcribed targets but also different sets of off-targets in the human background transcriptome. More than 900 of such off-targets with editing efficiencies up to 91%, largely explained by known PPR-RNA binding properties, were identified for PPR56. Engineering two crucial amino acid positions in its PPR array led to predictable shifts in target recognition. We conclude that plant PPR editing factors can operate in the entirely different genetic environment of the human nucleo-cytosol and can be intentionally re-engineered towards new targets.
Keywords: Genetics

Third‐Order Susceptibility of Lithium Niobate: Influence of Polarons and Bipolarons - Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero (physica status solidi (b))
The third‐order susceptibility of lithium niobate (LiNbO 3 ) is calculated within a Berry‐phase formulation of the dynamical polarization based on the electronic structure obtained within density‐functional theory (DFT). Maximum values of the order of m V are calculated for photon energies between 1.2 and 2 eV, i.e., in the lower half of the optical bandgap of lithium niobate. Both free and bound electron (bi)polarons are found to lead to a remarkable enhancement of the third‐order susceptibility for photon energies below 1 eV.

Bridging HPC Communities through the Julia Programming Language - Churavy, Valentin; Godoy, William F; Bauer, Carsten; Ranocha, Hendrik; Schlottke-Lakemper, Michael; Räss, Ludovic; Blaschke, Johannes; Giordano, Mosè; Schnetter, Erik; Omlin, Samuel; Vetter, Jeffrey S; Edelman, Alan
The Julia programming language has evolved into a modern alternative to fill existing gaps in scientific computing and data science applications. Julia leverages a unified and coordinated single-language and ecosystem paradigm and has a proven track record of achieving high performance without sacrificing user productivity. These aspects make Julia a viable alternative to high-performance computing's (HPC's) existing and increasingly costly many-body workflow composition strategy in which traditional HPC languages (e.g., Fortran, C, C++) are used for simulations, and higher-level languages (e.g., Python, R, MATLAB) are used for data analysis and interactive computing. Julia's rapid growth in language capabilities, package ecosystem, and community make it a promising universal language for HPC. This paper presents the views of a multidisciplinary group of researchers from academia, government, and industry that advocate for an HPC software development paradigm that emphasizes developer productivity, workflow portability, and low barriers for entry. We believe that the Julia programming language, its ecosystem, and its community provide modern and powerful capabilities that enable this group's objectives. Crucially, we believe that Julia can provide a feasible and less costly approach to programming scientific applications and workflows that target HPC facilities. In this work, we examine the current practice and role of Julia as a common, end-to-end programming model to address major challenges in scientific reproducibility, data-driven AI/machine learning, co-design and workflows, scalability and performance portability in heterogeneous computing, network communication, data management, and community education. As a result, the diversification of current investments to fulfill the needs of the upcoming decade is crucial as more supercomputing centers prepare for the exascale era.

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Lattice QCD noise reduction for bosonic correlators through blocking - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (International Conference on High Performance Computing in Asia-Pacific Region)

CP2K on the road to exascale - Kühne, Thomas; Plessl, Christian; Schade, Robert; Schütt, Ole (arXiv:2205.14741)
The CP2K program package, which can be considered as the swiss army knife of atomistic simulations, is presented with a special emphasis on ab-initio molecular dynamics using the second-generation Car-Parrinello method. After outlining current and near-term development efforts with regards to massively parallel low-scaling post-Hartree-Fock and eigenvalue solvers, novel approaches on how we plan to take full advantage of future low-precision hardware architectures are introduced. Our focus here is on combining our submatrix method with the approximate computing paradigm to address the immanent exascale era.

Parallel quantum chemistry on noisy intermediate-scale quantum computers - Schade, Robert; Bauer, Carsten; Tamoev, Konstantin; Mazur, Lukas; Plessl, Christian; Kühne, Thomas (Phys. Rev. Research)
A parallel hybrid quantum-classical algorithm for the solution of the quantum-chemical ground-state energy problem on gate-based quantum computers is presented. This approach is based on the reduced density-matrix functional theory (RDMFT) formulation of the electronic structure problem. For that purpose, the density-matrix functional of the full system is decomposed into an indirectly coupled sum of density-matrix functionals for all its subsystems using the adaptive cluster approximation to RDMFT. The approximations involved in the decomposition and the adaptive cluster approximation itself can be systematically converged to the exact result. The solutions for the density-matrix functionals of the effective subsystems involves a constrained minimization over many-particle states that are approximated by parametrized trial states on the quantum computer similarly to the variational quantum eigensolver. The independence of the density-matrix functionals of the effective subsystems introduces a new level of parallelization and allows for the computational treatment of much larger molecules on a quantum computer with a given qubit count. In addition, for the proposed algorithm techniques are presented to reduce the qubit count, the number of quantum programs, as well as its depth. The evaluation of a density-matrix functional as the essential part of our approach is demonstrated for Hubbard-like systems on IBM quantum computers based on superconducting transmon qubits.